PODCAST: An alternative way to improve EFL students’ listening and speaking performance - Marisa Yoestara; Zaiyana Putri (Englisia: Journal of Language, Education, and Humanities, 2018)
This article aims to view the impacts of using podcast in improving listening and speaking performance. As there is a trend of using ICT in language teaching growths, the authors intend to discuss about the media that can be used in enhancing students’ ability in listening skill and speaking performance. The authors collected the information related to the topic of this article from several sources such as, books, journal articels, and previous studies. From these sources, it can be concluded that podcast can bring many benefits in teaching listening and speaking for EFL learners.